Sugar-sweetened beverage affordability and the prevalence of overweight and obesity in a cross section of countries - Fabrizio Ferretti; Michele Mariani (BMC, 2019)
Abstract Background A key component of 'obesogenic environments' is the ready availability of convenient, calorie-dense foods, in the form of hyper-palatable and relatively inexpensive ultra-processed products. Compelling evidence indicates that the regular consumption of soft drinks, specifically carbonated and non-carbonated sugar-sweetened beverages (SSBs), has a significant impact on the prevalence of overweight and obesity. However, to implement country-level effective prevention programmes we need to supplement this evidence with quantitative knowledge of the relationships between overweight/obesity and the main determinants of SSB consumption, notably SSB prices and consumers' disposable income. Method Affordability considers the simultaneous effects of both price and disposable income on the buying decision. The purpose of this study was to investigate the effect of SSB affordability on the consumers' purchasing behaviour and weight-related health outcomes. Our study was divided into three parts. First, we computed SSB consumption and affordability for approximately 150 countries worldwide. Second, we estimated a demand function for SSBs to assess the impact of affordability on consumption at the country level. Third, we used a multivariate regression model and country data on the prevalence of overweight and obesity to test the role of SSB affordability in the current obesity epidemic. Results The analysis reveals that SSB affordability: 1) showed both a large variability across countries and a clear tendency to increase substantially with the level of economic development; 2) played a key role in determining cross-country differences in the amount of soft drink consumed per capita; and 3) was significantly associated with the prevalence rates of both overweight and obesity. Specifically, we show that a 10 % increase in SSB affordability was associated, on average, with approximately 0.4 more overweight/obese adults per 100 inhabitants. Conclusions By controlling for the main possible confounding factors, our results clearly indicate that affordability is a major driver of purchasing behaviours and is significantly associated with the prevalence rates of both overweight and obesity. We thus suggest a fiscal approach to curb SSB consumption based on the effectiveness of 'soda taxes' to affect the long-term dynamic of SSB affordability.